2009
DOI: 10.1007/s10798-009-9093-9
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework for developing the curriculum and delivery of technology education in early childhood

Abstract: The purpose of this article is to provide an overview of the analysis of the Early Childhood Education (ECE) curriculum in six countries involved in the UPDATE-project, and on that basis, propose a conceptual foundation for technology education in ECE that aims to enhance gender sensitive technology education in the continuum from early years to adulthood. The existing ECE curricula in the participating countries were analysed according to the general pedagogical approach as well as the contents specific to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 5 publications
(6 reference statements)
1
47
0
6
Order By: Relevance
“…Other teachers are of the view that they can detect a difference between what boys and girls play with and how they do it (cf. Turja et al, 2009). They exemplify with the fact that boys more often build garages and roads while girls construct objects to do with, for instance, farming.…”
Section: Preschool Teachers' Understanding Of Gendermentioning
confidence: 98%
See 2 more Smart Citations
“…Other teachers are of the view that they can detect a difference between what boys and girls play with and how they do it (cf. Turja et al, 2009). They exemplify with the fact that boys more often build garages and roads while girls construct objects to do with, for instance, farming.…”
Section: Preschool Teachers' Understanding Of Gendermentioning
confidence: 98%
“…Turja et al (2009) claim that girls generally have a lower self-confidence when it comes to activities which are seen as stereotypically male. Although building a tower with blocks is not a stereotypically male activity, it still seems likely that she does not dare to enter the play on the same terms as the boys; in this situation she therefore becomes a "helper" to the boys.…”
Section: Girls' Lack Of Self-confidencementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that interest and self-efficacy with respect to technology arise early in childhood (Turja, Endepohs-Ulpe, & Chatoney, 2009;Endepohls-Ulpe, Ebach, Seiter, & Kaul, 2012). As not all parents are interested in crafts and technology, or work in a technologyoriented field, we suggest that in order to raise the interest of those girls who will have no example from their family, it is important that schools take more responsibility for providing information and role models for these possible study and career options.…”
Section: Discussionmentioning
confidence: 99%
“…Freeman, 2007;Turja et al, 2009), enligt vilken leksaker och lekar följer stereotypa könsmönster; pojkar leker med bilar och lyftkranar, där tekniken ofta blir central i leken, medan flickor deltar i lekar med dockor och hästar där tekniken endast bildar bakgrund (t.ex. en hästhage).…”
Section: Det äR Ett Lite Längre Tema Som Handlar Om Vatten Men Jag Haunclassified